2015
DOI: 10.1075/lab.5.2.03ion
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of NPs in generic and existential contexts in L3 Brazilian Portuguese

Abstract: This paper examines the interpretation of NPs in generic and existential contexts in the acquisition of Brazilian Portuguese (BrP) as a third language (L3) by learners who speak English and a Romance language (Spanish, French or Italian). The paper examines whether transfer / cross-linguistic influence is from English, Spanish/French/Italian, or both, and whether it matters which language is the learners’ first language (L1) vs. their second language (L2). An Acceptability Judgment Task of NP interpretation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
10
0
3
Order By: Relevance
“…Ionin et al (2015) extended the previous study and examined the generic and existential interpretation of definite, indefinite and bare NPs. The BrP L3ers were L1 English–L2 Romance (Spanish, French or Italian) and L1 Spanish–L2 English adults.…”
Section: Genericity In Second Language/third Language Acquisitionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ionin et al (2015) extended the previous study and examined the generic and existential interpretation of definite, indefinite and bare NPs. The BrP L3ers were L1 English–L2 Romance (Spanish, French or Italian) and L1 Spanish–L2 English adults.…”
Section: Genericity In Second Language/third Language Acquisitionmentioning
confidence: 89%
“…The findings of two studies (Ionin, Montrul, Kim, & Philippov, 2011; Snape, Garcia Mayo, & Gürel, 2013) suggest that L2 genericity is largely determined by the way it is realized in the L1, but that learners show target-like accuracy in advanced stages of L2A. As for L3A, to our knowledge, only two studies in L3A investigated genericity, and indicated that prior L1 and L2 knowledge as well as L3 input intervened in genericity construction: Ionin, Grolla, Santos, and Montrul (2015), which built on Ionin, Grolla, Montrul, and Santos (2013).…”
Section: Genericity In Second Language/third Language Acquisitionmentioning
confidence: 96%
“…Overall, the results of the two studies demonstrated that the L2 influence on L3 phonology is conditioned by typology. More recently, Ionin et al (2015) conducted plural NP interpretation tests to assess L1-English L2-Spanish L3-Brazilian Portuguese learners (ESB) and L1-Spanish L2-English L3-Brazilian Portuguese learners (SEB) to ascertain how transfers occur in L3A. Their findings suggest that in determining the interpretation of plural NPs in their L3A, participants rely on the language they recognize as being structurally close to the L3, irrespective of whether it is their L1 or L2.…”
Section: Typological Primacy Model (Tpm)mentioning
confidence: 99%
“…Cada condição era apresentada na presença de um contexto, sendo enunciada após a apresentação de uma história, como foi feito nos estudos de Ionin et al (2015Ionin et al ( , 2018. Após o proferimento da sentença-teste pelo fantoche, o falante fornecia seu julgamento.…”
Section: Materiais E Métodosunclassified